Essential oil and composition of Tagetes minuta from Uganda.Larvicidal activity on Anopheles gambiae - Mugumya Kyarimpa, Christine; Böhmdorfer, Stefan; Wasswa, John; Kiremire, Benard T.; Omolo Ndiege, Isaiah; Kabasa, John David (Industrial Crops and Products, 2014)
As the search for alternatives to synthetic medicine goes on, several plants have been identified as possible natural insecticides, among which is Tagetes minuta. In this study essential oil from T. minuta was obtained by hydrodistillation. It was tested against the 3rd and 4th instar Anopheles gambiae to determine the larvicidal activity. Six different concentrations of this essential oil were studied and compared with thatof methyl parathion, a synthetic organophosphorus insecticide for 24 h. GC–MS results indicated the presence trans-ocimene 15.90%, I-verbenone 15% of limonene 8.02%, tegetone 3.56%, and 2-pinen-4-one7.84% as the major compounds in the essential oil. The LC50 was 2.9 mg/l while the LC90 was 3.29 mg/l after 2 h of exposure. After 6 h of exposure, the LC50 and LC90 were 2.31 mg/l and 2.68 mg/l, respectively,while after 12 h, it was 1.49 and 1.82 mg/l, respectively. After 24 h, the LC50 and LC90 were not determined because the mortality was 100%. Therefore effectiveness of essential oil from T. minuta is comparable to that of synthetic insecticides and can be studied further in lieu of becoming a possible alternative.
Keywords: Essential oil; Anopheles gambiae; Tagetes minuta; Methyl parathiona